(untitled) (Research, Society and Development, 2022)
Objective: The objective of this research was to evaluate stress in teachers in the five areas of Education (Early Childhood Education, Elementary School I and II, High School and University). Methods: A total of 125 teachers from Baixada Santista, SP, Brazil, were included. Physical and psychological stress in the their lives were evaluated, using the Marilda Lipp Stress Symptom Inventory (lSSI) test. Symptoms were assessed in the first 24 hours, 1 week and after 1 month. It was applied remotely, in a single application, from April to June 2021. Results: Out of the total of 125 teachers, 92 had stress and 33 had no stress. Out of the 111 female participants, 84 had stress and 27 had no stress, whereas out of the 14 male participants, 8 had stress and 6 had no stress. Of the 92 participants that showed stress, 5 participants were in the Alert Phase, 49 participants were in the Resistance Phase and 38 participants were in the Exhaustion Phase. 39 participants had Physical symptoms, 5 participants had Psychological symptoms and 48 participants had both symptoms. Conclusion: It is important to reflect on the importance of stress prevention within educational institutions, aiming to provide a better quality of life for teachers.